Metabolic characteristics of different phenotypes in reproductive-aged women with polycystic ovary syndrome - Wen, Xinling; Wang, Li; Bai, E. (Frontiers in Endocrinology, 2024)
Objective: Polycystic ovary syndrome (PCOS) is an endocrine metabolic disorder in reproductive-aged women. The study was designed to investigate the metabolic characteristics of different phenotypes in PCOS women of reproductive age. Methods: Four hundred and forty-two women with PCOS were recruited in this cross-sectional study. According to different phenotypes, all women were divided into three groups: chronic ovulatory dysfunction and hyperandrogenism group (OD-HA group, n=138), chronic ovulatory dysfunction and polycystic ovarian morphology group (OD-PCOM group, n=161), hyperandrogenism and polycystic ovarian morphology group (HA-PCOM group, n=143). The metabolic risk factors and prevalence rates of metabolic disorders among the three groups were compared. Results: The body mass index (BMI), waist circumference and waist to hip ratio (WHR) in women of OD-HA group and HA-PCOM group were significantly higher than that of women in OD-PCOM group (P<0.05). The serum insulin concentration, homeostasis model assessment of insulin resistance (HOMA IR) at 2h and 3h after oral glucose powder in women of OD-HA group and HA-PCOM group were significantly higher compared with OD-PCOM group (P<0.05). The serum total cholesterol (TC), triglyceride (TG) and low-density lipoprotein cholesterol (LDL-C) in women of OD-HA group and HA-PCOM group were significantly higher compared with OD-PCOM group (P<0.05). The prevalence rates of impaired glucose tolerance (IGT), type 2 diabetes mellitus (T2DM), insulin resistance (IR), metabolic syndrome (MS), nonalcoholic fatty liver disease (NAFLD) and dyslipidemia of women with PCOS were 17.9%, 3.6%, 58.4%, 29.4%, 46.6% and 43.4%, respectively. The prevalence rates of IGT, IR, MS, NAFLD and dyslipidemia of women in OD-HA group and HA-PCOM group were significantly higher compared with women in OD-PCOM group (P<0.05). T concentration (>1.67 nmol/L) and F–G score (>3) significantly increased the risk of metabolic disorders in women with PCOS (P<0.05). Conclusion: The phenotypes of OD-HA and HA-PCOM in PCOS women were vulnerable to metabolic disorders than OD-PCOM. So the metabolic disorders in PCOS women especially those with HA phenotype should be paid more attention in order to reduce long-term complications.